2016
DOI: 10.21450/rahis.v13i1.2944
|View full text |Cite
|
Sign up to set email alerts
|

Conhecendo a Experiência De Implantação Do Prontuário Eletrônico Do Paciente No Hospital De Base De São José Do Rio Preto

Abstract: RESUMOOs sistemas de Prontuário Eletrônico do Paciente (PEP) tornaram-se cada vez mais atrativos para instituições de saúde que buscam unir informações clínicas e administrativas. Realizado cinco anos após a implantação do PEP no Hospital de Base em São José do Rio Preto, este estudo tem por objetivo avaliar a experiência com a nova ferramenta, a partir da análise das principais vantagens e desvantagens deste sistema segundo profissionais da saúde. Esta pesquisa incluiu 68 profissionais da saúde vinculados ao … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…In the institutions that already use it, such as seen in the present study, it is possible to improve the use of computerized systems, by increasing the number of computers available for access (28) , employing more investment to avoid system failures (inoperative system) and in order to train and continue education, given that some health professionals still show resistance and difficulty to handle this type of documentation (27) . The mapping of 502 Nursing activities in North American hospitals (29) identified 21 of these as commonly being considered by 90% of nursing managers for daily decision making on Nursing staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the institutions that already use it, such as seen in the present study, it is possible to improve the use of computerized systems, by increasing the number of computers available for access (28) , employing more investment to avoid system failures (inoperative system) and in order to train and continue education, given that some health professionals still show resistance and difficulty to handle this type of documentation (27) . The mapping of 502 Nursing activities in North American hospitals (29) identified 21 of these as commonly being considered by 90% of nursing managers for daily decision making on Nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…However, the time consumed is significantly high, making it necessary to implement some strategies for its reduction, such as the implementation of electronic record keeping (27) .…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for major investments in systems, equipment and software, as these are essential for failures to be less and less frequent. 11 It was found that the need for assistance to work with information resources came from not or little training, as approximately 60% of the interviewed professionals received only one training and 16% said they had not received training, showing a weakness. There is a close relationship between training and the use of EMR and its use without difficulty by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a implementação ou aquisição de ferramentas comerciais pode significar quantidade substancial de recursos 6,9,10 .…”
Section: Introductionunclassified
“…O prontuário eletrônico do paciente (PEP) tornou-se a principal ferramenta com a qual médicos e equipes precisam lidar em suas atividades diárias. Entretanto, apesar dos aparentes benefícios trazidos pela adoção do PEP, o avanço dessa tecnologia no setor de saúde exige não só um investimento de alto custo por parte das instituições de saúde, como também uma capacitação dos profissionais de saúde e um estudo destinado a melhorar as práticas de registro 10,11 .…”
Section: Introductionunclassified